IMPROVING MANAGEMENT OF EARLY CHILDHOOD EDUCATION (PAUD) THROUGH IDENTIFICATION OF INSTITUTIONAL PROBLEMS - Hasni Noor; Riinawati R (Berajah Journal, 2021)
The success of managing early childhood education institutions depends on aspects of curriculum management, infrastructure, marketing, students, supervisors, and educators. One of the most important steps in the management of educators is because this management determines how educators provide facilities to develop the skills possessed by children so that they can achieve the desired educational goals. This study aims to improve PAUD management (early childhood education) by identifying system problems. This study uses a qualitative and descriptive research model. The research sample is the Professor of the Integrated Islamic Ukhuwah PAUD Banjarmasin. The results showed that the observations, attention, communication and personality of teachers and children had been carried out well. Teachers often consult children's questions which show that the Ukhuwah Banjarmasin Integrated Islamic PAUD teachers on average have carried out their duties well.